Crystallographic Analysis of a Full-length Streptavidin with Its C-terminal Polypeptide Bound in the Biotin Binding Site - Le Trong, Isolde; Humbert, Nicolas; Ward, Thomas R.; Stenkamp, Ronald E. (My University, 2006)
The structure of a full-length streptavidin has been determined at 1.7 Å resolution and shows that the 20 residue extension at the C terminus forms a well-ordered polypeptide loop on the surface of the tetramer. Residues 150–153 of the extension are bound to the ligand-binding site, possibly competing with exogenous ligands. The binding mode of these residues is compared with that of biotin and peptidic ligands. The observed structure helps to rationalize the observations that full-length mature streptavidin binds biotinylated macromolecules with reduced affinity.
Keywords: full-length streptavidin; crystallography; self-binding; protein/ligand interactions